Efektivitas Penerapan Model Discovery Learning dan Inquiry Terhadap Keterampilan Berpikir Kritis Pembelajaran Subtema Perubahan Bentuk Energi Kelas III Gugus Sudirman - Krisda Amelia; Suhandi Astuti (Peneliti.net, 2020)
The purpose of this research was to test the effectiveness of discovery learning models in enhancing critical thinking skills in learning subtheme changes in the energy shape of third grade students of the Sudirman Elementary School. This type of research is quasi experiment or quasi experiment. The research design used was static-group comparison. The results of the study used the t test with a significance level of 5% showing tcount 2.943> t table 3.160 with the significance value indicating sig <0.05 (0.004 <0.05), then H0 was rejected and Ha was accepted. So it was concluded that the discovery learning model was effective in increasing the critical thinking skills of students in class III of Sudirman Elementary School.